A Prestressed Soft Gripper: Design, Modeling, Fabrication, and Tests for Food Handling - Zhongkui Wang; Torigoe, Yuuki; Hirai, Shinichi (IEEE robotics and automation letters, 2017)
This study presented a prestressed soft gripper fabricated with 3-D printing technology. The gripper can realize a large contact area while grasping and simultaneously generate large initial opening without deflating the soft actuators. The soft actuator was 3-D printed as two separate parts: the soft chambers with a rigid connector and a cover to seal the chambers. The chamber part was stretched longitudinally and sealed by gluing the cover onto it. The actuator was then released, and an initial curl occurred due to the remaining prestress. Finite element (FE) simulations were performed to validate this concept and the designed structure. Actuator fabrication and experimental tests were presented, and agreements between the FE simulations and test results were achieved. A gripper consisting of four prestressed actuators was constructed and experimentally tested by picking-and-placing food materials in different weights and different sized containers. To adapt to objects of different sizes and shapes, the gripper base was designed to have two configurations and two openings. The results showed that the prestressed gripper could stably handle various types of food and still remain compact with a simple supporting system.